INTERVENSI PERUBAHAN PERILAKU KESEHATAN ORANG DENGAN HIV/AIDS (STUDI KASUS PADA KELOMPOK DUKUNGAN SEBAYA SOLO PLUS DI SURAKARTA) - Demartoto, Argyo (UNIVERSITAS SEBELAS MARET (UNS), 2019)
People living with HIV/AIDS (PLWHA) hope to live healthily, so that Peer Support Group (PSG) responds to the PLWHA’s psychosocial and medical needs. The objective of research was to study the Solo Plus PSG’s intervention to the change of PLWHA’s health behavior in Surakarta. This qualitative research with case study approach was conducted on the chairperson and members of Solo Plus, People Affected by HIV/AIDS (PABHA), Surakarta AIDS Commission, health workers, and NGOs caring about AIDS in Surakarta. Data was collected through observation, in-depth interview, and documentation, while data validation was carried out using source triangulation. The explanatory analysis technique used in this case study was Simmel’s social shape and Schramer’s U theories. The result of research showed that Solo Plus held monthly routine meeting for information on the session attended by many parties like psychiatrist, herbalist, Voluntary Counseling and Testing (VCT); psychosocial support members; improved the capacity of organization and PSG members with training, policy advocacy and public awareness through harings with government; initiated the establishment of satellite PSG in surrounding areas to support PLWHA; participated actively in socializing the prevention of HIV to community; gave testimony in many events; supported Care Support and Treatment (CST) care, case management, such as VCT referral, CST, Local Health Insurance, CD 4 test, liver and kidney function test, Prevention of Mother to Child Transmission (PMTCT); provided Supplementary Food; and facilitated PLWHA in Penitentiary, visited hospitals and houses; supported the sustainable livelihood of PSG members; and developed network. Keywords: Community intervention, behavior change, peer support group AbstrakOrang dengan HIV/AIDS (ODHA) berharap dapat sehat, sehingga Kelompok Dukungan Sebaya (KDS) merespons atas kebutuhan psikososial medis ODHA. Tujuan penelitian ini mengkaji intervensi KDS Solo Plus terhadap perubahan perilaku kesehatan ODHA di Surakarta. Penelitian kualitatif dengan pendekatan studi kasus ini dilakukan terhadap ketua dan anggota Solo Plus, Orang Hidup dengan HIV/AIDS (OHIDA), Komisi Penanggulangan AIDS Kota Surakarta, petugas pelayanan kesehatan, dan LSM peduli AIDS di Surakarta. Data dikumpulkan dengan observasi, wawancara mendalam dan dokumentasi, serta untuk menguji validitas data digunakan triangulasi sumber. Teknik analisis eksplanasi studi kasus ini menggunakan teori bentuk sosial dari Simmel dan teori U dari Schramer. Hasil penelitian menunjukkan bahwa Solo Plus melakukan pertemuan rutin bulanan untuk info sesi dari berbagai pihak, seperti psikiatri, herbalis, Voluntary Counseling and Testing (VCT); memberi dukungan psikososial; peningkatan kapasitas organisasi dan anggota KDS dengan pelatihan; advokasi kebijakan dan penyadaran publik melalui audiensi dengan pemerintah; menginisiasi pembentukan KDS satelit di sekitarnya untuk mendukung ODHA; terlibat aktif dalam sosialisasi pencegahan HIV ke masyarakat; testimoni di berbagai even; mendukung layanan Care Support and Treatment (CST); manajemen kasus, seperti rujukan VCT, CST, Jaminan Kesehatan Daerah; test CD 4, test fungsi hati dan ginjal, Prevention of Mother to Child Transmision (PMTCT); Pemberian Makanan Tambahan, dan pendampingan ODHA di Lembaga Pemasyarakatan, kunjungan di rumah sakit maupun di rumah; mendukung keberlanjutan mata pencaharian anggota KDS serta mengembangkan jaringan kerja. Kata kunci : Intervensi komunitas, perubahan perilaku, kelompok dukungan sebaya